2021
DOI: 10.1177/0300060520986369
|View full text |Cite
|
Sign up to set email alerts
|

Layer-specific strain for assessing the effect of naringin on systolic myocardial dysfunction induced by sepsis and its underlying mechanisms

Abstract: Objective This study aimed to investigate the protective effects of naringin on myocardial deformation and oxidative responses in rats with sepsis-induced myocardial dysfunction (SIMD). Methods Global and segmental layer-specific longitudinal strain (LS) was assessed by speckle tracking echocardiography. Serum levels of creatine kinase, lactate dehydrogenase, superoxide dismutase, and malondialdehyde were measured. The activity of cleaved caspase-3 was determined by immunohistochemistry. Protein expression lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…In these researches, NAR treatment reduced infarct size compared to the non-treatet group. Moreover, NAR was reported to show its protective role through inhibition of inflammatory response [15], oxidative stress [16], and preservation of mitochondrial structure [17]. Here, the cell viability in cell group treated with NAR at dose of 80 µM and 160 µM was not significantly different (p>0,05).…”
Section: Nar Reduces H9c2 Cell Death In Hr Injurymentioning
confidence: 69%
“…In these researches, NAR treatment reduced infarct size compared to the non-treatet group. Moreover, NAR was reported to show its protective role through inhibition of inflammatory response [15], oxidative stress [16], and preservation of mitochondrial structure [17]. Here, the cell viability in cell group treated with NAR at dose of 80 µM and 160 µM was not significantly different (p>0,05).…”
Section: Nar Reduces H9c2 Cell Death In Hr Injurymentioning
confidence: 69%
“…In LPS-treated adipose-derived stem cells, the expression of KEAP1 is significantly increased and correlates with a drop in the expression of Nrf2 as well as decreased levels of antioxidant enzymes 58 . In septic cardiomyopathy, administration of naringin was shown to suppress KEAP1 expression and therefore restore the expression of Nrf2, leading to improved mitochondrial function 59 . Our results showed that sepsis does not alter cardiac KEAP1 expression, but induces instead its phosphorylation at T85 through upregulation of STK3.…”
Section: Discussionmentioning
confidence: 99%
“…More than 95% of sepsis is caused by bacterial infection, and the release of endotoxin lipopolysaccharides (LPS) caused by bacterial infection is the main factor leading to sepsis ( Sun et al, 2021 ). When the body is invaded by LPS, Toll-like receptor 4 on the surface of macrophages recognizes LPS and activates intracellular signal transduction of macrophages to produce a large number of pro-inflammatory cytokines, such as TNF-a, IL-1β, IL-6, IL-12, etc.…”
Section: Introductionmentioning
confidence: 99%